The Effect of Problem Based Learning Model of Understanding of Science Concepts as Seen in the Factors of Critical Thinking Abilities of Grade V Elementary School Students - Rahman, Nahar Nur; Gunarhadi, Gunarhadi; Chumdari, Chumdari (Jurnal Mamangan, 2023)
Miscopception wrong concepts in science learning is a major challenge for elementary school (SD) students, which can hinder the learning process and form a less scientific mindset. This article discusses the influence of Problem Based Learning and Inquiry Learning models on understanding science concepts, as well as the role of critical thinking skills in supporting this understanding. This research uses a quasi-experimental method with a 2x2 factorial design.The results of the research show that there are significant differences in understanding concepts between students taught with Problem Based Learning and Inquiry Learning. The average conceptual understanding score for students taught with Problem Based Learning is 72.07, while for students taught with Inquiry Learning it is 69.65. In addition, students with high critical thinking skills have an average conceptual understanding score of 81.15, while students with low critical thinking skills have an average score of 60.5. The research results also show that there is an interaction between the learning model and critical thinking skills on students' understanding of concepts. Problem Based Learning has proven to be more effective in increasing understanding of concepts, especially for students with high critical thinking skills.In conclusion, the learning model has a significant effect on understanding science concepts, with Problem Based Learning being a more effective strategy than Inquiry Learning. Apart from that, critical thinking skills play an important role in increasing understanding of science concepts in elementary schools.